Investigating the spill overs and connectedness between financial globalization, high-tech industries and environmental footprints: Fresh evidence in context of China - Shahzad, Umer; Ferraz, Diogo [UNESP]; Nguyen, Huu-Huan; Cui, Lianbiao (Elsevier, 2022)
China faces the challenge of promoting high-tech industries and concomitantly reduces ecological footprints. This research analyzes the directional spillover impacts and connectedness for financial and trade globalization, high-tech industries, and environmental footprints of China. The authors used the data of financial globalization, trade globalization, economic complexity, middle and high-tech industrial contribution, and ecological footprint of China throughout 1996Q1 to 2019Q4. The empirics contribute to the debate on the impacts of the high technology industry, financial globalization for the environmental sustainably in the era of the digital economy. The study finds positive spillover effects from financial globalization (FGI), and economic complexity towards ecological footprints. Further, the high technology industrial contribution has a less significant impact on reducing environmental footprints. Overall, the findings are robust to the presence of structural change effects and the cleaner production objectives for China's case. Concomitantly, the empirical findings allow us to report innovative conclusions and implications regarding the sustainable development goals (SDG-7, 10), high-industry, and environmental sustainability in China.
Keywords: China; Ecological footprint; Financial globalization; High-tech industries; Sustainable development goals